Analisis Kelayakan Usaha Petshop di Kota Probolinggo - Adela Wafiq Azizah; Arga Christian Sitohang (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is to assess the profitability and viability of pet shop enterprises in Probolinggo City. Six pet shop entrepreneurs from Probolinggo City served as informants for this study. This study's analytical methodologies included overall costs, revenues, income, and company feasibility. This study found that the average total costs incurred were IDR 17,105,497, the average income was IDR 22,823,530, and the average income was IDR 5,718,033. The findings of calculating the three business feasibility metrics for six pet store entrepreneur informants in Probolinggo City show that the average R/C ratio is 1.37 > 1, while the average B/C ratio is 0.37 > 0. And the average ROI value attained is 23.75%, which is greater than one percent. As a result, the pet shop business in Probolinggo City is considered reasonable to operate.